Incidence and implications of spleniculi: a five-year experience - Govindaraj, Sridar; Roshini, A. P. (International Surgery Journal, 2018)
Background: Spleniculi or accessory spleen, is a congenital anomaly occurring in 10% of individuals. Spleniculi resembles normal spleen in structure and in immunological function. Certain hematological and radiological investigations can indicate residual splenic function. They can enlarge following splenectomy and be the source of recurrent symptoms in those operated on for hematological disorders. Methods: Authors did a retrospective study in a tertiary care hospital to estimate the incidence and to describe the location and number of spleniculi in patients undergoing splenectomy, both elective and emergency, over a 5-year period - October 2013 to October 2018. Total patients included was 186. Results: Majority of the patients were in the age group of 18-45years. 16 (8.6%) had spleniculi, found incidentally and confirmed histopathologically. Hematological disorders, out of which Idiopathic Thrombocytopenic Purpura 70 (49.6%) was the most common indication. Commonest location was in the hilum, 12 (75%), second being, near the tail of pancreas. 1 patient presented with a left hypochondriac mass, which was confirmed as enlarged spleniculi on histopathology, post - relook surgery. Conclusions: Accessory spleens are asymptomatic and have a high chance of being overlooked during splenectomy, which could be one of the causes of relapse in hematological disorders.